Mental Health Situation in the Society - Suarez Pulido, Mateo Adolfo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Mental health is an important aspect of human development. For years, we realized the valor ofphysical health for the human being in all aspects of life. In contrast, we do not give the sameimportance to mental health and its effects on personal, social, and professional development. Whenwe talk about mental health, we do not even perceive it as a serious illness, and this only makes theproblem worse. Finally, society must understand that mental health is as or even more important thanphysical health, and it should be given the priority it needs.